Pembelajaran Bahasa Arab Melalui Media Radio dan Televisi - Ahmad Muzammil (Institut Agama Islam Darusssalam Blokagung, 2023)
Learning Arabic in Indonesia has existed since the arrival of Islam in the first century of Hijriyah. Learning Arabic was initially focused on understanding the meaning of the verses of the Qur'an, the hadiths of the Prophet and to understand the sources of Islamic law. Therefore Arabic is taught in all educational institutions, starting from salaf pesantren, madrasah Diniyah and also formal institutions ranging from elementary level institutions to tertiary level. Based on the existing facts that the Indonesian people are not of Arab ethnicity. but from Javanese, Madurese, Sundanese and other ethnicities, Arabic is a second language and even a third language after the regional language and national language. Thus, in the process of learning Arabic, many problems are found. One of the main problems is the reluctance of students to learn Arabic from the start. Thus, Arabic teachers should use media that is easy and can arouse students' motivation in learning Arabic, such as learning Arabic with radio and TV media. After conducting research and studying Arabic language learning using radio and TV media, it can be concluded that the application of learning Arabic using radio and TV media is not suitable for all people, learning with radio and TV media is only suitable for middle and high level students.